ANALISIS TRANSIEN PENSTOK: PENGARUH WAKTU PENUTUPAN - Haryadi Mumin (UPPM Politeknik TEDC Bandung, 2015)
Hydroelectricity is eligible energy resource to be developed in the future because of a variety of advantages.Hydropower potential on a river in North Sulawesi has been known for a long time. With rising electricitydemand today, the potential energy of the water will soon be realized into hydropower. Existing site conditionsdo not allow for the use of surge tanks as dampening device for water hammer effects. This researchwillperform transient and water hammer analysis as basic of the penstock design and turbine selection. Waterhammer transient analysis was carried out with varying the main valve closure time from 5 s, to 120 s. It can beconcluded that the sharp decrease water hammer effect on the main valve closure time will end when theclosure time was 30 s. After that, decrease water hammer parameters were no longer significant.Keyword : transien, penstok, water hammer, waktu penutupan.